Pengaruh Good Corporate Governance Terhadap Kinerja Keuangan pada Perusahaan Industri Produk Makanan Pertanian - Olivia, Siska; Sartono, Sartono; Risal, Risal (Program Studi Akuntansi Universitas Panca Bhakti, 2025)
This study aims to analyze the influence of good corporate governance (GCG) as proxied by the board of commissioners, board of directors, audit committee, institutional ownership, and managerial ownership. Financial performance is measured by Return on Assets (ROA). The study uses a quantitative approach with secondary data from financial reports sourced from company documents using documentation techniques, literature reviews, and internet research. The sampling technique used purposive sampling/characteristic-based sampling, so the sample in this study consisted of 38 agricultural companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The analysis was conducted using multiple linear regression with SPSS. The results show that the board of commissioners and institutional ownership have no significant effect on financial performance, but the audit committee and managerial ownership have a significant negative effect on financial performance, while the board of directors has a significant positive effect on financial performance.